Life in the land of the midnight sun: are northern lizards adapted to longer days? - Uller, T; Olsson, M (2003)
The relative importance of genetic and environmental factors for explaining differences in trait distributions between populations is one of the major issues in evolutionary biology. In ectotherms, temperature can have a major impact on morphology, physiology, and life history strategies, and has often been inferred to explain differences between populations. In species with active thermoregulation, however, the ambient temperature may not be as important as the opportunity for thermoregulation. We studied growth in juvenile common lizards (Lacerta vivipara) originating from two environments differing in such thermal opportunity (i.e. day length). The populations differed significantly in their norms of reaction, with lizards experiencing long days in the wild showing a steeper increase in growth rate with increasing thermal opportunity. The environment with longer days also has a lower mean temperature tn the wild, and in accordance with evolutionary predictions, lizards from this population had higher endurance at low temperatures. Both populations showed genetic variation in degree of phenotypic plasticity in growth rate as evident from the extensive crossing in norms of reaction.